A Comprehensive Coronal and Axial Bone Dimension and Cartilage Thickness Evaluation of the Distal Humerus: Age and Sex Differences. (December 2021) - Misir, Abdulhamit; Gunay, Ali Eray; Oguzkaya, Sinan; Uzun, Erdal; Kizkapan, Turan Bilge; Yildiz, Kadir Ilker; Ozcamdalli, Mustafa
Objective: There are limited data on bone dimension and cartilage thickness of the distal humeral articular surface. This study aimed to evaluate sex- and age-related bone dimension and cartilage thickness differences and assess the effect of cartilage thickness on distal humeral shape. Design: Elbow magnetic resonance images of 180 healthy participants were evaluated. Cartilage thicknesses of the trochlea and capitellum were measured at 19 points using coronal and axial images. In addition, bone diameters were measured from the flexion-extension axis to the 19 points on the coronal and axial magnetic resonance images. Sex differences were evaluated, and the correlation between age and measurement parameters was assessed. Results: Significant sex differences regarding the diameters of the axial trochlear bone, coronal lateral trochlear bone, and medial capitellar bone, cartilage thickness at the apex of the lateral trochlear ridge in the axial and coronal plane and at the most lateral point of the capitellar articular surface in the axial plane were observed. A negative correlation was observed between age and axial plane trochlear bone dimensions and between age and coronal plane lateral trochlear and medial capitellar bone dimensions. No significant correlation was found between cartilage thickness and bone dimensions. Conclusions: Bone dimension and cartilage thickness at the distal humerus vary according to sex and age. The data could be used in the donor site selection and graft preparation while osteochondral autograft transfer and allograft transplantation, and in the development of gender-compatible hemiarthroplasty implants.